Impact of tumor necrosis factor antagonist combination and anti-integrin therapies on body mass index in inflammatory bowel disease: A cross-sectional study - Shehab, Mohammad; Alali, Ali; Al-Hindawi, Ahmed; Alsayegh, Abdulwahab; Aldallal, Usama; Abdullah, Israa; Albaghli, Abbas; Alrashed, Fatema; Alfadhli, Ahmad; Bessissow, Talat (Frontiers in Medicine, 2023)
Background: The impact of biologic therapies on body mass index (BMI) in patients with inflammatory bowel disease (IBD) is unclear. This study investigates any associations between BMI, type of IBD, and the type of medications taken among patients with IBD with varying weight categories. Methods: A cross sectional study was performed in an IBD tertiary care center. Data was obtained from patients with IBD attending outpatient clinics from January 1st, 2021 until November 1st, 2021. Adult patients, older than 18 years, with a diagnosis of Crohn’s disease (CD) or ulcerative colitis (UC) were recruited. The primary outcome was the association between BMI and medication used in IBD. The secondary outcome was the association between BMI and disease type and location in patients with IBD. Results: The study included a total of 528 patients of which, 66.5% have CD. Patients with normal weight comprises 55.9% of the participants, while those who are underweight, overweight or obese are 3.4%, 28.2% and 12.5% respectively. None of the underweight patients had ulcerative colitis. Among the normal weight, overweight and obese BMI categories, 34.6 % vs 36.2% vs 31.8% had ulcerative colitis respectively. Patients who are on tumor necrosis factor inhibitors (anti-TNF) with an immunomodulator (anti-TNF combination), are more likely to be overweight or obese than patients who are not on anti-TNF combination (OR 2.86, 95% CI 1.739-4.711, p<0.001). Patients on vedolizumab are twice as likely to be overweight or obese than patients not on vedolizumab (OR 2.23, 95% CI 1.086-4.584, p<0.05). Patients with ileocolonic Crohn’s disease are more likely to be overweight or obese compared to other subtypes of CD (OR 1.78, 95% CI 1.14-2.77, p=0.01). Conclusions: Many patients with IBD are either obese or overweight. Patients with IBD who are on anti-TNF combination therapy or vedolizumab monotherapy are more likely to be obese and overweight. In addition, patients will ileocolonic CD are more likely to be obese or overweight.